Suppression of Ghost Targets in Focusing Azimuth Periodically Gapped SAR Raw Data with Complex Iterative Thresholding Algorithm - Qian, Yulei; Zhu, Daiyin (Proceedings of the IEEE Sensor Array and Multichannel Signal Processing Workshop, 2020)
An algorithm is presented in this paper to focus the azimuth periodically gapped SAR (Synthetic Aperture Radar) raw data. The proposed algorithm mainly contains phase multiplication in range frequency domain and sparse reconstruction in range Doppler domain. The phase multiplication in range frequency domain aims to acquire sparser data in range Doppler domain. Then, the complex iterative thresholding algorithm is utilized to reconstruct the complete SAR data in range Doppler domain. The iterative thresholding algorithm is extended to cope with the complex SAR data. Afterwards, the traditional SAR focusing methods are capable of obtaining image from the recovered data. The proposed method performs well on suppressing ghost targets induced by gapping. Point target simulation is implemented to assess the validity of the proposed method. In addition, real SAR data experiment is also utilized to demonstrate the effectiveness of the proposed method.